Prolonged Radiant Exposure of the Middle Ear during Transcanal Endoscopic Ear Surgery. (16th March 2015) - Shah, Parth V.; Kozin, Elliott D.; Remenschneider, Aaron K.; Dedmon, Matthew M.; Nakajima, Hideko Heidi; Cohen, Michael S.; Lee, Daniel J.
Abstract : Transcanal endoscopic ear surgery (EES) provides a high‐resolution, wide‐field view of the middle ear compared with the conventional operating microscope, reducing the need for a postauricular incision or mastoidectomy. Our group has shown in cadaveric human temporal bone studies that radiant energy from the endoscope tip can quickly elevate temperatures of the tympanic cavity. Elevated temperatures of the middle ear are associated with acute auditory brainstem response shifts in animal models. In EES, proposed methods to decrease middle ear temperature include frequent removal of the endoscope and the use of suction to rapidly dissipate heat; however, the routine application of such cooling techniques remains unknown. Herein, we aim to quantify the duration that the tympanic cavity is typically exposed to the endoscope during routine endoscopic middle ear surgery. We find that the tympanic cavity is exposed to the endoscope without a cooling mechanism for a prolonged period of time.